2004
DOI: 10.1002/clc.4960270406
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 123I‐BMIPP single‐photon emission computed tomography in patients with congestive heart failure: Effect of angiotensin ii type‐1 receptor blockade

Abstract: SummaryBackground: Heart failure is a major and growing public health problem with a high mortality rate. Although recent studies have demonstrated that a variety of metabolic and/or neurohumoral factors are involved in the progression of this syndrome, the precise mechanisms responsible for this complex condition are poorly understood.Hypothesis: To examine 123 I-␤-methyl-iodophenylpentadecanoic acid (BMIPP) kinetics in the early phase soon after tracer injection in patients with congestive heart failure (CHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Despite the clear beneficial effects of angiotensin converting enzyme inhibitors and angiotensin receptor antagonists in slowing the progression of HF, there are little data on the metabolic consequences of suppression of the effects of angiotensin in HF. Indirect measurement of myocardial fatty acid metabolism using noninvasive imaging of the fatty acid analog BMIPP shows that HF patients have less cardiac accumulation of BMIPP and a faster washout rate from the myocardium than in healthy controls and that 6 mo of treatment with either enalipril or candesartan improved cardiac function and increases the accumulation and slows the rate of BMIPP washout (450,502), suggestive of greater fatty acid uptake and clearance after treatment. The interpretation of these findings is complicated by difficulties in quantitatively relating BMIPP kinetics to myocardial fatty acid uptake and oxidation (228,234,363).…”
Section: B Long-term Metabolic Therapy To Slow Heart Failure Progresmentioning
confidence: 99%
“…Despite the clear beneficial effects of angiotensin converting enzyme inhibitors and angiotensin receptor antagonists in slowing the progression of HF, there are little data on the metabolic consequences of suppression of the effects of angiotensin in HF. Indirect measurement of myocardial fatty acid metabolism using noninvasive imaging of the fatty acid analog BMIPP shows that HF patients have less cardiac accumulation of BMIPP and a faster washout rate from the myocardium than in healthy controls and that 6 mo of treatment with either enalipril or candesartan improved cardiac function and increases the accumulation and slows the rate of BMIPP washout (450,502), suggestive of greater fatty acid uptake and clearance after treatment. The interpretation of these findings is complicated by difficulties in quantitatively relating BMIPP kinetics to myocardial fatty acid uptake and oxidation (228,234,363).…”
Section: B Long-term Metabolic Therapy To Slow Heart Failure Progresmentioning
confidence: 99%
“…The retention and esterification in the myocardium slows down ␣-oxidation rates (26). Nonetheless, some studies suggest that BMIPP washout in the early phase obtained with dynamic SPECT imaging may be a marker of heart failure and might be valuable in therapy assessment (92). However, its applications in human cardiac imaging due to this retention are limited.…”
Section: Cardiac Fatty Acid Metabolism With Spectmentioning
confidence: 99%
“…It was shown that 123 I-BMIPP washout was enhanced at baseline and significantly improved after treatment with ARB. It was concluded that improvement in fatty acid metabolism may represent a new mechanism for beneficial effects of ARBs [39].…”
Section: Renin-angiotensin-aldosterone System In Heart Failurementioning
confidence: 99%